A meta‐ethnography of developing and living with post‐burn scars. Issue 1 (25th September 2022) - Bayuo, Jonathan; Wong, Frances Kam Yuet; Lin, Rose; Su, Jing Jing; Abu‐Odah, Hammoda
Abstract: Introduction: Post‐burn scarring is often cosmetically unappealing and create discomfort. This makes it crucial to understand the experience of individuals living with scars which can offer insights into their recovery. This review sought to develop an in‐depth understanding of living with post‐burn scars. Design: A systematic review and meta‐ethnography approach were employed. We utilized an interpretive approach to inductively generate codes. These codes were examined iteratively using a constant comparison strategy following which they were re‐interpreted to formulate themes which formed the basis of undertaking a narrative synthesis. Results: Twenty‐five studies were retained. The analytical process yielded two themes: emergence of a new identity and living with the redefined self. The experience of living with scars is entwined with the initial trauma as the scars served as a permanent reminder of the injury. Emergence of a new identity involved a process of meaning making, mourning the loss of the old self, confronting the new self, reconciling the remains of the old self with the new, rebuilding a new identity, and navigating through functional restrictions. These processes were particularly challenging for persons involved in self‐immolation. Positive coping and changing one's perspective emerged as strategies to facilitate living with the redefined self. Conclusion: Living with scars is a challenging process which is more difficult for persons whose injuries are due to self‐immolation (act of burning oneself). The findings highlight a latent yet ongoing process towards subjective recovery. Clinicians need to be aware of the processes and incorporate these into rehabilitation programmes. Clinical relevance: Burn survivors need ongoing professional support to adjust to and live with the scars. Victims of self‐immolation should be considered for early psychosocial support.